Two Distinct Mechanisms Mediate the Involvement of Bone Marrow Cells in Islet Remodeling: Neogenesis of Insulin-Producing Cells and Support of Islet Recovery. Issue 5 (May 2015) - Iskovich, Svetlana; Goldenberg-Cohen, Nitza; Sadikov, Tamila; Yaniv, Isaac; Stein, Jerry; Askenasy, Nadir
We have recently reported that small-sized bone marrow cells (BMCs) isolated by counterflow centrifugal elutriation and depleted of lineage markers (Fr25lin - ) have the capacity to differentiate and contribute to regeneration of injured islets. In this study, we assess some of the characteristics of these cells compared to elutriated hematopoietic progenitors (R/O) and whole BMCs in a murine model of streptozotocin-induced chemical diabetes. The GFP bright CD45 + progeny of whole BMCs and R/O progenitors progressively infiltrate the pancreas with evolution of donor chimerism; are found at islet perimeter, vascular, and ductal walls; and have a modest impact on islet recovery from injury. In contrast, Fr25lin - cells incorporate in the islets, convert to GFP dim CD45 - PDX-1 + phenotypes, produce proinsulin, and secrete insulin with significant contribution to stabilization of glucose homeostasis. The elutriated Fr25lin - cells express low levels of CD45 and are negative for SCA-1 and c-kit, as removal of cells expressing these markers did not impair conversion to produce insulin. BMCs mediate two synergistic mechanisms that contribute to islet recovery from injury: support of islet remodeling by hematopoietic cells and neogenesis of insulin-producing cells from stem cells.